Fundos constitucionais e o financiamento do desenvolvimento via bancos públicos : uma análise da distribuição de recursos do FNE - Ferreira, Ester William (2013)
The purpose of this study is to analyze the dynamics of the distribution of resources from the Constitutional Fund for Financing of the Northeast (FNE) in order to verify how this distribution occurs, by number and value of credit loans, in federal units served by the Fund and, within these, in their communities, in the years of 1999-2010. It starts from the recognition that the Constitutional Funds, established by the 1988 Federal Constitution, are an important source of financing for productive activities and infrastructure in the North, Northeast and Midwest. Besides that, they have been created to foment the development of these regions in order to contribute with the reduction of regional inequalities. With the purpose of to observe the distribution of the resources of these Funds, in particular FNE is necessary to understand that this distribution does not happen separately, but within the context of a monetary production economy, where money, credit and banks play a fundamental role in economic growth and regional development, as advocates by Post Keynesian approach. According to this approach, the distribution of the regional resources tends to have a significant concentration in most dynamic regions and economically integrated into larger agents (greater economic integration), even in the case of funds released by public banks, such as the FNE, Funds administered by the Northeast Bank of Brazil (BNB). After reviewing the legal framework that underlies the functioning of the Constitutional Funds, in order to identify major changes since its institutionalization, we proceeded to study the information provided by the Ministry of National Integration and the BNB. Through the Simple Correspondence Analysis (ANACOR), processed in Stata software, we obtained the results of correspondence between two variables: volume of credit FNE by municipality/PIB by municipality and Human Development Index 2000, which allowed understanding the degree of interdependence between the level of funding credit of municipalities served by the FNE and the level of their development, respectively. Finally, with the discussion of the results, this thesis aims to contribute to the deepening of the reflections on the possibilities and the difficulties founded in using the Constitutional Funds as a major funding instruments for public policy for regional development.